CLAUSES CONTRADICTING MAIN PURPOSE OF THE CONTRACT - Sansawet , Wittawat; Pongsapan, Munin (Journal of MCU Nakhondhat, 2023)
The purpose of this research was to study legal problems related to agreements that conflict with the main purpose of the contract, and to suggest means to implement laws related to such agreements in Thailand, using method of documentary research comparing Thai laws with French and English laws. This research studied Thai and foreign laws through legal research, textbooks, articles, theses, court rulings, and comparative descriptions, including the impact of law enforcement in Thailand and abroad. The results of the study revealed that 1) there is no law regarding the agreement that contradicts main purpose of the contract in Thai law, only traces of law in clauses restricting or excluding liability for breach of contract and such principles were not mentioned among the scholars and there is no application of this principle to the practice; 2) an agreement that is contrary to the main purpose of the contract, if applied in accordance with current Thai law, may be considered to have an objective that is in conflict with public order and deemed void under the Civil and Commercial Code, Section 150, which is a broad principle with no criteria for consideration, or it may require the interpretation of the intention and the interpretation of the contract under the Civil and Commercial Code, Section 171 and Section 368, which does not have clear and specific criteria and may cause problems in finding the true intent of the parties. Therefore, I thought that specific provisions concerning the agreement that conflict with the main objectives of the contract should be added to clarify the law and provide certain criteria for consideration in order to achieve the main objectives of the contract, which are the intentions of the parties to make a contract.